2020
DOI: 10.1007/s43032-020-00385-2
|View full text |Cite
|
Sign up to set email alerts
|

Placental Compartmentalization of Lipid Metabolism: Implications for Singleton and Twin Pregnancies

Abstract: Introduction. The study of placental lipid metabolism in uncomplicated pregnancies has not been 2 developed in the literature to date. Its importance lies in expanding the knowledge of placental function to 3 enable comparison with pathological pregnancies in future research. The aim of the present study was to 4 compare the lipid metabolic activity and storage of the maternal and fetal sides of the placenta in healthy 5 pregnancies. Moreover, we compare singleton vs. twin pregnancies to determine if placental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…A decrease in the gene expression of FAO enzymes in pre-eclampsia, especially on the fetal side of the placenta, leads to the lower utilization of FFA by the placenta with the accumulation of triglycerides on the fetal side, as previously reported [ 16 ]. Theoretically, the pathogenic sequence can start with decreased placental FAO, which would increase the FFA and triglyceride placental and maternal serum levels, leading to immune-resistance, lipotoxicity, and finally, endothelial damage.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A decrease in the gene expression of FAO enzymes in pre-eclampsia, especially on the fetal side of the placenta, leads to the lower utilization of FFA by the placenta with the accumulation of triglycerides on the fetal side, as previously reported [ 16 ]. Theoretically, the pathogenic sequence can start with decreased placental FAO, which would increase the FFA and triglyceride placental and maternal serum levels, leading to immune-resistance, lipotoxicity, and finally, endothelial damage.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, placental FAO disorders might play a role in the pathophysiology of pre-eclampsia. In addition, we have previously demonstrated that in healthy pregnant women, the maternal side of the placenta is more active in the esterification of fatty acids, whereas lipid storage concentrates more on the fetal side [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy early pregnancy, insulin stimulates lipogenesis. However, in mid and late pregnancy, insulin leads to an intensification of lipolysis of fatty deposits, leading to maternal hyperlipidemia, specifically due to hypertriglyceridemia and FFA, to provide energy for the growing fetus [ 28 , 52 , 53 , 54 ]. In preeclampsia, there is an increase in FFA [ 11 , 52 ], hypertriglyceridemia [ 55 , 56 ], and higher oxidized-LDL in maternal serum [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of fatty acid oxidation (FAO) in placental explants was performed according to the method previously described by our group [ 25 , 26 , 27 , 28 ]. It was quantified as nanomoles of [3H]-palmitate per gram of tissue per hour (nmol/g/h).…”
Section: Methodsmentioning
confidence: 99%
“…Our result showed that the levels of TG in elbow vein and umbilical cord blood for 4 groups were statistically different, and the TG level of macrosomia group was significantly increased. TG cannot be directly used by the fetus through the placental barrier, so it needs to be hydrolyzed into small molecular substances by lipase and then transported through the placenta into the umbilical vein blood, which is absorbed by the fetus, resulting in the increase of neonatal weight [18].…”
Section: Discussionmentioning
confidence: 99%